Influence of structural rigidity of Cu(II)/Mo(VI) complexes on the photoconductivity of film polymeric composites. (13th August 2018) - Davidenko, N. A.; Kokozay, V. N.; Buvailo, H. I.; Makhankova, V. G.; Studzinsky, S. L.; Davidenko, I. I.
Abstract: Novel film polymeric composites based on the non-photoconducting polyvinyl butyral with heterometallic complexes (NH4 )4 n [Cu(en)(H2 O)][P2 Mo5 O23 ] n ·3.5 n H2 O (1 ) and (NH4 )2 n [Cu(en)2 ][Cu(en)(H2 O)][P2 Mo5 O23 ] n ·3 n H2 O (2 ) [en = ethylenediamine] have been prepared. Both compounds are similar and contain Strandberg anions [P2 Mo5 O23 ] 6– linked to Cu-diamine species. The main structural difference between complexes is the presence of additional bridging [Cu(en)2 ] fragments in2, which provide an extra connectivity between the neighboring polyoxometalates. However, the different saturations and relaxation times of the photoresponse, as well as different activation energies, are shown. The variability of the photoconducting properties can be explained by the influence of a chain rigidity on the transport of non-equilibrium charge carriers.